Self Help Groups Under Swarnjayanti Swarojgar Yojana: Grass Root Constraints of Dairy Owners - Subodh Kumar; Hema Tripathi (Indian Journal of Extension Education, 2014)
Data were collected from 208 members of 52 SHGs comprising 50 per cent male and 50 per cent female groups through structured interview schedule from Faizabad district of Eastern Uttar Pradesh. The study revealed that the lack of remunerative price for milk and milk products, improper supply and high cost of veterinary services and medicines as well as lack of training regarding scientific dairy husbandry were the severe problems perceived by the SHG members ranked at I, II and III place, respectively. At group level, major constraints perceived by them were; illiteracy followed by improper supervision by block officers, untimely credit disbursement, complicated bank procedures, intra-group conflict and non-cooperation by family members in descending order.